2018
DOI: 10.1248/bpb.b17-00970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultivation Month and Genetic Background on Phenolic Content of <i>Citrus tachibana</i> Peel

Abstract: Species of the Citrus genus are known as rich sources of phenolic compounds. Peels of Citrus tachibana and Citrus unshiu are used in herbal formulations, sometimes in similar ways. In this study, we examined the effects of plant maturity and genetic background on the total phenolic contents and quantities of specific flavonoids in C. tachibana peel. In addition, we compared these values in C. tachibana and C. unshiu peels. The total phenolic contents and the contents of nobiletin, tangeretin, and hesperidin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Some studies have reported that the content of phenolic acids, which exhibit strong antioxidant activity, decreases depending on the ripeness of fruits. 20,21 The results of this study are consistent with those of previous literature, where it is illustrated that the antioxidant capacity of CRCP might be reduced with delayed harvesting. Besides, Ledesma-Escobar et al have reported that phenolic acid and flavonoids reached maximum concentration at week 5 and 12, respectively, and then decreased significantly during growth, which might relate to the concentration change of phenylalanine, a precursor in the phenol pathway.…”
Section: Resultssupporting
confidence: 92%
“…Some studies have reported that the content of phenolic acids, which exhibit strong antioxidant activity, decreases depending on the ripeness of fruits. 20,21 The results of this study are consistent with those of previous literature, where it is illustrated that the antioxidant capacity of CRCP might be reduced with delayed harvesting. Besides, Ledesma-Escobar et al have reported that phenolic acid and flavonoids reached maximum concentration at week 5 and 12, respectively, and then decreased significantly during growth, which might relate to the concentration change of phenylalanine, a precursor in the phenol pathway.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that neutrophil elastase is indirectly involved in collagen and elastin degradation through MMP-1 and MMP-2 activation as well as by direct degradation [5]. It has also been reported that exposure to UV and particulate matter 2.5 (PM 2.5) induces excessive ROS generation, leading to DNA damage in normal cells and increased MMP (collagenase) levels, which can promote skin aging [15][16][17][18]. It is considered that supplements that prevent elastase and collagenase activity, as well as superoxide generation, are useful as ingredients in cosmetics that slow down skin aging.…”
Section: Discussionmentioning
confidence: 99%
“…Assay for SOD-like activity was performed as described previously [15]. The reaction mixture contained the extracts, 0.2 M Tris-HCl buffer (pH 7.8), 0.1 mM EDTA-2Na, 0.1 mM xanthine, 0.05 mM nitro blue tetrazolium, and 0.05 U xanthine oxidase.…”
Section: Assay For Sod-like Activitymentioning
confidence: 99%
See 2 more Smart Citations